Persepsi Masyarakat Madani Terhadap Asuransi Syariah - Ratu Humaemah; Najmi Hillalliyati (Syar'Insurance: Jurnal Asuransi Syariah, 2023)
The rapid development of sharia insurance in Indonesia is an achievement for Muslims as well as representing significant economic growth for the people. But on the other hand, it cannot be denied that there are still many obstacles to be faced, especially with regulations and public perceptions of the sharia system. This study aims to obtain information regarding the perceptions of Serang City civil society towards sharia insurance and is presented descriptively in the form of a narrative. The phenomenological approach aims to explain a phenomenon or the reality of something that describes the characteristics of the subject under study. In this study in general put forward a good response to sharia insurance. Whether it's the people of Serang City who have been members of conventional insurance, or who have never joined as members of any insurance but already know and understand the insurance scheme.